Oclusão percutânea de forame oval patente em pacientes acima de sessenta anos com histórico de acidente vascular cerebral - Sabedotti, Marcelo (My University, 2024)
Fundamentals: The prevalence of patent foramen ovale (PFO) is about 27%,decreasing to 20% after age 80. PFO is associated with paradoxical embolism, which can cause ischemic stroke (IS). IS with no identifiable cause is common in 25% to 40% of cases, and PFO is frequently found in these patients. The prevalence of PFO is nearly three times higher in elderly patients with IS of unknown etiology compared to patients of the same age with a known cause of IS, suggesting that patients in this age group may also benefit from PFO closure. Objectives: The primary objective was to assess the recurrence of IS or transient ischemic attack (TIA) during clinical follow-up. Secondary objectives included verifying the occurrence of procedure-related complications, onset of atrial fibrillation (AF), and reduction in the use of anticoagulants. Methods: A retrospective cohort study of 36 patients over 60 years old with a history of IS who underwent percutaneous closure of PFO. Results: The average age was 69.6±6.5 years, and 55.5% were male. No complications occurred during the procedures. An echocardiogram was performed 30 days after the intervention, with no residual shunts found. During follow-up of 4.9±3.6 years, there were no occurrences of IS, TIA, or procedure-related AF. The use of anticoagulants reduced from 41.7% to 5.6% (p=0.03). Conclusions: Percutaneous closure of PFO for the prevention of cerebrovascular events in individuals over 60 years old with a history of IS is effective, safe, and has a low risk of complications, potentially reducing the risk of bleeding by decreasing the use of anticoagulants. [resumo fornecido pelo autor]
Fundamentos: A prevalência de forame oval patente (FOP) é de cerca de 27%, diminuindo para 20% após os 80 anos. O FOP está relacionado à embolia paradoxal, que pode causar acidente vascular cerebral isquêmico (AVCi). O AVCi sem causa identificável é comum em 25% a 40% dos casos e o FOP é frequentemente encontrado nestes pacientes. A prevalência de FOP é quase três vezes maior em pacientes idosos com AVCi sem identificação etiológica em comparação com pacientes da mesma idade com uma causa conhecida de AVCi, sugerindo que pacientes desta faixa etária também podem se beneficiar do fechamento do FOP. Objetivos: Objetivo primário foi avaliar a recorrência de AVCi ou ataque isquêmico transitório (AIT) no seguimento clínico. Objetivos secundários foram verificar a ocorrência de complicações relacionadas ao procedimento, início de FA e redução do uso de anticoagulantes. Métodos: Coorte retrospectiva com 36 pacientes com mais de 60 anos e AVCi prévio submetidos a oclusão percutânea de FOP. Resultados: Média de idade de 69.6±6.5 anos e 55.5% homens. Nenhuma complicação ocorreu nos procedimentos. Ecocardiograma foi realizado 30 dias após a intervenção, não foi encontrado shunts residuais. No seguimento de 4.9 ±3.6 anos, não ocorreu AVCi, AIT, nem FA relacionada ao procedimento. O uso de anticoagulantes reduziu de 41.7% para 5.6% (p=0.03). Conclusões: Oclusão percutânea de FOP para prevenção de eventos cerebrovasculares em indivíduos com mais de 60 anos com AVCi prévio é efetiva, segura e de baixo risco de complicações, podendo reduzir o risco de sangramento pela redução do uso de anticoagulantes. [resumo fornecido pelo autor]
Keywords: Forame oval patente; AVC Isquêmico; Idosos - Pacientes; Acidente vascular cerebral - Pacientes; Foramen oval permeable; Ischemic stroke; Older people - Patients; Cerebrovascular disease - Patients